The Contribution of Investment to the Government and Local Communities in the Kampar Regency Riau - Rida Jelita; Thamrin S; Abd Thalib (Rechtsnormen: Journal of Law, 2024)
Background. This study was conducted to analyze and assess the barriers in the implementation of oil palm plantation contributions to the government and local communities in Kampar Regency, Riau. Purpose. The samples of this research are oil palm plantation companies and local communities located in Kampar Regency, Riau. Method. n its discussion, the researcher uses a normative juridical approach, the normative juridical approach used in this research is an approach through positive law, namely positive legal rules to find the legality of the data used is secondary data where journals, articles, books, reviews, papers, and others become the main source in this research. Results. The results of this study indicate that 1) the analysis of the contribution of development in the field of capitalization of oil palm plantations by plantation companies to the government and society has not been significant to economic growth. 2) the implementation of oil palm companies towards the government and the people of Kampar Regency, Riau is a different understanding and implementation in perceiving the law, the effectiveness of the budget year is still lacking, the budget is not absorbed, and employment is not absorbed. Conclusion. In addition, field research can also be used as a complement, namely interviews supported by primary data.